Faktor – Faktor yang Mempengaruhi Produksi Buncis di Desa Antapan, Kecamatan Baturiti, Kabupaten Tabanan - ARDIANSAH, DANY NOVAN; SARJANA, I DEWA GEDE RAKA; DJELANTIK, A.A.A. WULANDIRA SAWITRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.8, No.3, Juli 2019, 2019)
Factors that Influence the Production of Beans in Antapan Village, Baturiti Sub-District, Tabanan Regency Bean is a horticultural commodity that has potential and health benefits, and its consumption can increase because of the FAO recommendations and an increase in population, but the production of beans is volatile. This condition causes no adequate national bean consumption and reduces the bean farmers' income. The purpose of the study was to determine the factors that influence the bean production in the village of Antapan. The research location was determined intentionally. The sampling method used a census method for all bean farmers in Antapan Village, totalling of 30 people.The research method uses the Cobb-Douglas production function. The research findings indicate that the F test results of six variables: seeds, labor, organic fertilizer, NPK fertilizer, fungicides, and insecticides affect simultaneously. Partially only organic fertilizer and NPK fertilizer had an effect (P <0,05) on the bean production.